Study of the Characterization of Side Population Cells in Endometrial Cancer Cell Lines: Chemoresistance, Progestin Resistance, and Radioresistance - Liu, Bing-jie; Xu, Qi-ying; Yu, Wei-dong; Li, Na; Yao, Tian; Zhao, Li-jun; Wang, Jian-liu; Wei, Li-hui; Li, Xiao-ping (Frontiers in Medicine, 2020)
Introduction: Radiotherapy, combined regimens as platinum-paclitaxel chemotherapy and/or endocrine therapy is an important adjuvant treatment after surgery for endometrial cancer(EC). While, the resistance to them remain unclear. In our study, to separate the characteristics of side population (SP) cells from EC cell lines, study the mechanism of Taxol-resistance, progestin resistance and radioresistanc ,and provide the basic for EC. Methods: SP cells from EC cell lines HEC-1A, Ishikawa and RL95-2 were separated by Hoechst 33342 staining and flow cytometry analysis. The expression of breast cancer resistance protein (BCRP) in SP cells and non-SP cells from HEC-1A was examined by immunocytochemistry, and the radiation-resistant and Taxol-resistant characteristics of SP cells and non-SP cells were compared by MTS. Ishikawa, Ishikawa-SP, and Ishikawa-non-SP cells incubated with MPA were selected for cell apoptosis assays by using flow cytometry. The expression of caspase-3 was examined by immunocytochemistry, and autophagy was detected by MDC staining. Results: Small proportions of SP cells, namely, 1.44%±0.93%, 2.86%±3.09%, and 2.87%±1.29%, were detected in HEC-1A, Ishikawa and RL95-2, respectively. There was a stronger clone formation efficiency for the SP cells than for non-SP cells in HEC-1A [(6.02±1.17)% vs.(0.53±0.20)%, P=0.001], and there was a significant difference in the rate of tumourigenicity between the SP cells and non-SP cells in HEC-1A (87.5% vs. 12.5%). There were higher levels of BCRP expression (P=0.001) and resistance to Taxol and radiation (P<0.05) in the SP cells than in non-SP cells. After MPA treatment, the apoptosis rates were significantly different among the Ishikawa, Ishikawa-SP and Ishikawa-non-SP groups [(4.64±0.18)%, (4.01±0.43)%, and (9.3±0.67)%; (P=0.05)], and the expression of Caspase-3 in the Ishikawa group was higher than that in Ishikawa-SP group. The autophagic activity of the Ishikawa-SP cells was the strongest, while the autophagic activity of Ishikawa-non-SP was the weakest. Conclusions: There is a significant enrichment in SP cells among different EC cell lines, and these SP cells be more resistant to Taxol, MPA and radiation therapy. The overexpression of BCRP among SP cells may be the cause of resistance to Taxol, progestin and radiotherapy, which may be related to apoptosis and autophagic activity.